Anatomy and variability of "Cuvierichelys parisiensis", a geoemydid turtle that crosses the Eocene-Oligocene boundary in Belgium - Pérez-García, Adán; Smith, R.; Smith, T. (Journal of Iberian Geology, 2016)
Abundant material of turtles from the early Oligocene site of Boutersem-TGV (Boutersem, Belgium), is presented here. No information on the turtles found there was so far available. All the turtle specimens presented here are attributable to a single freshwater taxon that is identified as a member of Geoemydidae, Cuvierichelys. It is the first representative of the ‘Palaeochelys s. l.–Mauremys’ group recognized in the Belgian Paleogene record. This material, which allows to know all the elements of both the carapace and the plastron of the taxon, cannot be attributed to the only species of the genus Cuvierichelys so far identified in the Oligocene, the Spanish form Cuvierichelys iberica. The taxon from Boutersem is recognized as Cuvierichelys parisiensis. Thus, both the paleobiogeographic and the biostratigraphic distributions of Cuvierichelys parisiensis are extended, its presence being confirmed for the first time outside the French Eocene record. The validity of some European forms is refuted, and several characters previously proposed as different between Cuvierichelys iberica and Cuvierichelys parisiensis are recognized as subjected to intraspecific variability.